Konsep Islam Moderat dan Implikasinya Terhadap Pendidikan Islam (Studi Pemikiran KH. Bisri Musthofa) - Zhamroni, Fery_Zhamroni; Shohib, Muhammad (Al-Mau'izhoh: Jurnal Pendidikan Agama Islam, 2024)
The purpose of this research is to examine the thoughts of KH. Bisri Musthofa related to the concept of moderate Islam, to then have implications for the development of Islamic education in Indonesia. This study uses a qualitative approach to the type of literature review (library research). Data collection uses the document study method, while the data analysis technique is carried out by content analysis and historical analysis. there are six stages in the content analysis method, namely: unitizing, sampling, recording, reducing, abductively inferring, narrating. then proceed with the validity of the test related to the validity of the data under review. The results showed that the concept of moderate Islam according to KH. Bisri Musthofa are: First, the concept of integration. Second, balance. Third, freedom and equality. Fourth, benefit and priority. The implications of the concept of moderate Islam on Islamic education initiated by KH. Bisri Musthofa includes several values. Among them namely; First, Integration: independence, responsibility, and qana'ah. Second, balance: love for the motherland, love for peace, and respect for others. Third, Freedom and equality: honest, fair, and optimistic. Fourth, Benefit and virtue: civilized, disciplined, patient, humble, and awareness.